Improved Methods for the Preparation of Fish Ball from the Unwashed Mixed Minces of Low-Cost Marine Fish - Hoque, MS; Nowsad, AAKM; Hossain, MI; Shikha, FH (Progressive Agriculture, 2014)
Fish ball was prepared from the unwashed mince blend of 5 low-cost marine fishes (LMF) viz., red jewfish (Johnius argentatus), sea cat fish (Tachysurus thalassinus), jeweled shad (Ilisha filigera) horse mackeral (Megalaspis cordyla) and skipjack tuna (Sarda orientalis) of the Bay of Bengal. Six different blends composition from 5 individual minces of Low-cost Marine Fish (LMF) were prepared by blending 15 to 30% of the individuals minces. Fish ball was prepared from such mince blends by improving the textural strength of the products through different cooking process, ingredients and spices. Textural quality was determined in terms of softness/firmness (S/F) and chewiness/ rubburiness (C/R). Gel forming ability of the individual minces varied in great extent due to their compositional differences. Among the six blends tested, blend C with higher proportion of mince had come from red jewfish, sea cat fish and horse mackerel showed highest gel strength. In mince blend C, composition of red jewfish, sea cat fish, horse mackerel, jeweled shad and skipjack tuna were 30, 20, 20, 15 and 15%, respectively. Unwashed and washed individual minces and the mince blend C were incubated at different temperature regime from 35° to 55° and then cooked at 90° or 100°C. Among the different heating regimes, unwashed mince blend C showed the highest gel strength at 50°C for 1 hr incubation temperature. Further cooking of the incubated gel at 100°C optimally increased the gelling ability. The quality attributes of fish ball prepared under different cooking process (two-step heating, boiling, broiling and autoclaving) were analyzed. In two-step cooking, fish ball heated at 50°C for 30 minutes and further cooked at 100°C for 30 minute obtained a very good textured and nice mouth-felt fish ball. Texture and flavor of ball was affected by washing of mince but sensory qualities were unaffected. DOI: http://dx.doi.org/10.3329/pa.v18i2.18203 Progress. Agric. 18(2): 189 - 197, 2007